2010
DOI: 10.1002/cncr.25689
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐137 promoter methylation is associated with poorer overall survival in patients with squamous cell carcinoma of the head and neck

Abstract: BACKGROUND:The overall 5-year survival rate of approximately 60% for head and neck cancer patients has remained essentially unchanged over the past 30 years. plays an essential role in cell-cycle control at the G1/S-phase checkpoint. However, the aberrant miR-137 promoter methylation observed in squamous cell carcinoma of the head and neck (SCCHN) suggests a tumor-specific molecular defect that may contribute to disease progression. METHODS: The goal of this study was to assess, in formalin-fixed, paraffin-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 57 publications
4
81
1
1
Order By: Relevance
“…Previous studies have confirmed that the aberrant methylation of the miR-137 promoter contributes to miR-137 silencing (Langevin et al 2010(Langevin et al , 2011Dang et al 2013). In the present study, we speculated that the continuous downregulation of miR-137 might reflect an increasing level of methylation, forming a feedback loop that increases AjBHMT levels and decreases in miR-137 levels to further increase the concentration of AjBHMT.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have confirmed that the aberrant methylation of the miR-137 promoter contributes to miR-137 silencing (Langevin et al 2010(Langevin et al , 2011Dang et al 2013). In the present study, we speculated that the continuous downregulation of miR-137 might reflect an increasing level of methylation, forming a feedback loop that increases AjBHMT levels and decreases in miR-137 levels to further increase the concentration of AjBHMT.…”
Section: Discussionsupporting
confidence: 65%
“…Mammalian miRNAs appear to target a wide variety of cellular functions using these posttranscriptional control mechanisms, including cellular proliferation and differentiation (Fazi et al, 2007;Lowenberg, 2008;Langevin et al, 2011). In the last few years, it has become evident that miRNA expression is deregulated in human cancer, resulting in specific oncogenic events, reviewed in Calin and Croce (Garzon et al, 2006) and Esquela-Kerscher and Slack (Esquela-Kerscher and Slack, 2006).…”
mentioning
confidence: 99%
“…Apart from the microRNA itself, the methylation status of miR-137 promoter has potential clinical value. Methylated miR-137 is a potential prognostic marker in HNSCC and is associated with survival (Langevin et al, 2011).…”
Section: Mir-137 [Mature Sequence: 59 -Uuauugcuuaagaauacgcguag -81 (Mmentioning
confidence: 99%